Chemical and thermal influence of the [4Fe-4S](2+) cluster of A/G-specific adenine glycosylase from Corynebacterium pseudotuberculosis - Eberle, Raphael Joseph [UNESP]; Coronado, Monika Aparecida [UNESP]; Caruso, Ícaro Putinhon [UNESP]; Lopes, Debora de Oliveira; Miyoshi, Anderson; Azevedo, Vasco; Arni, Raghuvir Krishnaswamy [UNESP] (Elsevier B.V., 2015)
The gram-positive bacteria Corynebacterium pseudotuberculosis, the causative agent of caseous lymphadenitis in livestock significantly reduces productivity and often causes death. The adenine/guanine-specific DNA glycosylase (MutY) prevents mutations in the DNA of the pathogen and a unique feature of the MutY protein family is the [4Fe-4S](2+) cluster that interlinks two protein subdomains. MutY from C. pseudotuberculosis was expressed in E. coli and purified, the CD experiments indicate a high content of alpha-helices and random coiled secondary structure and a typical near-UV CD fingerprint for the [4Fe-4S](2+) cluster. EDTA and copper sulfate possess a strong destabilizing effect on the [4Fe-4S](2+) cluster. UV-vis and fluorescence spectroscopy results demonstrate that between pH 3.0 and 4.0 the integrity of the [4Fe-4S](2+) cluster is destroyed. To investigate the thermal stability of the protein differential scanning calorimetry and fluorescence spectroscopy were used and the T-m was determined to be 45 degrees C. The analysis presented provides information concerning the protein stability under different physio-chemical conditions.
Keywords: C. pseudotuberculosis; MutY; [4Fe-4S](2+) cluster; DNA repair; Spectroscopic method; Secondary and tertiary structure